Comment on "Potential short‐term earthquake forecasting by farm animal monitoring" by Wikelski, Mueller, Scocco, Catorci, Desinov, Belyaev, Keim, Pohlmeier, Fechteler, and Mai. (30th October 2020) - Zöller, Gert; Hainzl, Sebastian; Tilmann, Frederik; Woith, Heiko; Dahm, Torsten
Abstract: Based on an analysis of continuous monitoring of farm animal behavior in the region of the 2016 M6.6 Norcia earthquake in Italy, Wikelski et al., 2020; (Ethology, 126(9), 2020, 931) conclude that animal activity can be anticipated with subsequent seismic activity and that this finding might help to design a "short‐term earthquake forecasting method." We show that this result is based on an incomplete analysis and misleading interpretations. Applying state‐of‐the‐art methods of statistics, we demonstrate that the proposed anticipatory patterns cannot be distinguished from random patterns, and consequently, the observed anomalies in animal activity do not have any forecasting power.